2019
DOI: 10.1002/mawe.201700198
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of deep rolling at different temperatures on the near surface microstructure and residual stress state of steel AISI 304

Abstract: The consequences of deep rolling at cryogenic temperature, room temperature and high temperature were investigated for steel X5CrNi18‐10 (AISI 304). Near surface microstructures, martensite content and residual stresses were analyzed. It is shown that, applying different deep rolling temperatures, the near surface states of the processed specimen are altered in a characteristic way. Particularly important is that different depth distributions of strain hardening, martensite volume fraction and residual stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The 3D-plot depicted clearly reveals that the maximum -martensite phase fraction is present at a distance of about 0.075 mm to 0.125 mm from the surface. Compared to the residual stress depth profile (Figure 8) in the longitudinal direction, this is apparently the area undergoing the highest Hertzian pressure during the deep rolling process [36]. After the -martensite phase fraction reaches its maximum, the amount decreases constantly.…”
Section: Characterization Of the Near Surface Propertiesmentioning
confidence: 87%
“…The 3D-plot depicted clearly reveals that the maximum -martensite phase fraction is present at a distance of about 0.075 mm to 0.125 mm from the surface. Compared to the residual stress depth profile (Figure 8) in the longitudinal direction, this is apparently the area undergoing the highest Hertzian pressure during the deep rolling process [36]. After the -martensite phase fraction reaches its maximum, the amount decreases constantly.…”
Section: Characterization Of the Near Surface Propertiesmentioning
confidence: 87%
“…Gharbi et al [13] detected a hardened layer of 800 µm with surface hardness of approximately 500 HV 0.1 after deep rolling of AISI 304, the machined condition presented a hardened layer of 400 µm and surface hardness of 380 HV 0.1 . Also considering the treatment of AISI 304 Kongthep et al [16] detected an increase on surface hardness reaching a depth of approximately 0.4 mm. Kloos et al [17] investigated the influence of deep cold rolling over the fatigue resistance of pieces produced with DIN 37CrS4 steel.…”
Section: Introductionmentioning
confidence: 99%
“…The change on residual stresses characteristics from tensile to compressive after deep rolling of AISI 304 was also observed by Gharbi et al [18], the machined surface presented values of 339 MPa, and after deep rolling the measured values were -383 MPa. Kongthep et al [16] observed compressive residual stresses on depths up to 1 mm after deep rolling AISI 304 with a force of 500 N When the burnishing is conducted on a milling machine or machining center, it is called Low Plasticity Burnishing (LPB), whose task is to increase the surface quality of the machined sample. On this case there are not many restrictions regarding the workpiece geometry or the tool path movement [7].…”
Section: Introductionmentioning
confidence: 99%
“…Following the TWIP and TRIP effect, new deformation mechanisms, namely the shear-band-induced plasticity (SIP) [27], the microband-induced plasticity (MBIP) [28], the slip-band refinement-induced plasticity (SRIP) [29] or the dynamic slip band refinement (DSBR) [30], have been reported. A detailed summary of these deformation mechanisms is presented in [31]. In HMnS, the SFE itself is strongly influenced by the alloying concept as well as the deformation temperature, highlighting the influence of these two parameters on the active deformation mechanisms [5,13,14,18,32].…”
Section: Introductionmentioning
confidence: 99%